1996
DOI: 10.1002/lt.500020604
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality in patients with coronary artery disease undergoing orthotopic liver transplantation

Abstract: Thirty-two patients with coronary artery disease who underwent liver transplantation between 1990 and 1994 were identified. Coronary artery disease was managed medically (n = 9), by angioplasty (n = l), or surgically (n = 22) prior to liver transplantation. Two patients underwent simultaneous coronary artery bypass gralting and liver transplantation. Complete preoperative cardiac evaluation was performed in all patients. Perioperative and postoperative morbidity and mortality were retrospectively determined. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(53 citation statements)
references
References 4 publications
(2 reference statements)
1
51
1
Order By: Relevance
“…Two out of 4 had also had a previous myocardial infarction b A total of 19 out of 33 cirrhotic patients with diabetes mellitus had been diagnosed with diabetes before the diagnosis of liver cirrhosis c Similar results were obtained after the exclusion of patients with hepatocellular carcinoma (data not shown) d Twenty-seven out of 28 cirrhotic patients with a history of hypertension had been diagnosed with arterial hypertension before the diagnosis of liver cirrhosis may actually contribute to the overall morbidity in this patient group. This is also in accordance with the high morbidity and mortality seen in patients with liver cirrhosis and CAD undergoing liver transplantation [24]. Two Italian groups have previously reported that liver cirrhosis is associated with low cardiovascular morbidity [4,12].…”
Section: Discussionsupporting
confidence: 72%
“…Two out of 4 had also had a previous myocardial infarction b A total of 19 out of 33 cirrhotic patients with diabetes mellitus had been diagnosed with diabetes before the diagnosis of liver cirrhosis c Similar results were obtained after the exclusion of patients with hepatocellular carcinoma (data not shown) d Twenty-seven out of 28 cirrhotic patients with a history of hypertension had been diagnosed with arterial hypertension before the diagnosis of liver cirrhosis may actually contribute to the overall morbidity in this patient group. This is also in accordance with the high morbidity and mortality seen in patients with liver cirrhosis and CAD undergoing liver transplantation [24]. Two Italian groups have previously reported that liver cirrhosis is associated with low cardiovascular morbidity [4,12].…”
Section: Discussionsupporting
confidence: 72%
“…Although there is no specific age limitation to LT, 14,15 older liver transplant recipients have been shown to have poorer long-term outcomes than younger patients, 16 in part because of their increased risk of cancer 17 and coronary artery disease. 18 Medical comorbidities and functional status are important factors in deciding who will undergo LT, and thus, younger patients are more likely to receive transplants because of fewer comorbidities and better functional status. Another important factor is the social support available to a patient who will undergo a major operation with a prolonged recovery time, and the need for close adherence to medications, lab testing, and clinic visits after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cardiac events are recognized as an important cause of death in patients undergoing liver transplantation [11, 12], especially in those known to have preexistent CAD. In response, the AASLD has recommended preoperative cardiac stress testing to detect occult CAD in “high-risk” ESLD patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…Because preexistent CAD is associated with increased cardiac mortality [11] only 11/393 patients (3%) that underwent liver transplantation had known preexistent CAD. Of the 350 LT patients who otherwise met “high-risk” AASLD criteria, 268 or 77% underwent a cardiac stress or imaging study to rule out significant coronary artery stenosis.…”
Section: Discussionmentioning
confidence: 99%